Analisis Strategi Pemasaran Untuk Meningkatkan Penjualan Motor Bekas Win Motor di Padang Pariaman - Nurofik, Agus; Trismiyanti, Dessy; Nini, Nini (Pustaka Galeri Mandiri, 2024)
This study aims to analyze the marketing strategies implemented by Win Motor in an effort to increase sales of used motorbikes in Padang Pariaman. The research method used is descriptive qualitative with data collection through interviews, observations, and documentation. The results of the study indicate that 1 Win Motor has implemented various marketing strategies, such as competitive pricing, promotions through social media and personal networks, and offering attractive after-sales services. However, there are still several aspects that need to be improved, such as diversification of distribution channels and development of customer loyalty programs. This study provides recommendations for Win Motor to optimize its marketing strategy so that it can achieve higher sales targets.